A gut microbial peptide and molecular mimicry in the pathogenesis of type 1 diabetes - Girdhar, Khyati; Huang, Qian; Chow, I-Ting; Vatanen, Tommi; Brady, Claudia; Raisingani, Amol; Autissier, Patrick; Atkinson, Mark A; Kwok, William W; Kahn, C Ronald; Altindis, Emrah (Proceedings of the National Academy of Sciences - PNAS, 2022)
Type 1 diabetes (T1D) is an autoimmune disease characterized by the destruction of pancreatic β-cells. One of the earliest aspects of this process is the development of autoantibodies and T cells directed at an epitope in the B-chain of insulin (insB:9-23). Analysis of microbial protein sequences with homology to the insB:9-23 sequence revealed 17 peptides showing >50% identity to insB:9-23. Of these 17 peptides, the peptide, found in the normal human gut commensal , activated both human T cell clones from T1D patients and T cell hybridomas from nonobese diabetic (NOD) mice specific to insB:9-23. Immunization of NOD mice with insB:9-23 peptide mimic or insB:9-23 peptide verified immune cross-reactivity. Colonization of female NOD mice with accelerated the development of T1D, increasing macrophages, dendritic cells, and destructive CD8 T cells, while decreasing FoxP3 regulatory T cells. Western blot analysis identified -reacting antibodies in sera of NOD mice colonized with and human T1D patients. Furthermore, adoptive transfer of splenocytes from -treated mice to NOD/SCID mice enhanced disease phenotype in the recipients. Finally, analysis of human children gut microbiome data from a longitudinal DIABIMMUNE study revealed that seroconversion rates (i.e., the proportion of individuals developing two or more autoantibodies) were consistently higher in children whose microbiome harbored sequences capable of producing the peptide compared to individuals who did not harbor it. Taken together, these data demonstrate the potential role of a gut microbiota-derived insB:9-23-mimic peptide as a molecular trigger of T1D pathogenesis.